A Influência Da República De Platão Na Política De Al-Farabi - Batista, Ana Paula [UNIFESP] (2018)
This Work Aims To Analyze The Political Works Of The Muslim Philosopher Al-F"R"B". This Thinker Is One Of The Most Important Historical Figures Of The Falsafa (Term That Dominates The Philosophy In Arabic) And He Is In The Origin Of The Development Of The Greek Philosophy In The Islamic Lands. Some Of His Writings Sought To Establish A Harmony Between The Greek Philosophers, Plato And Aristotle, Marking A Tradition In This Context. It Is Based On This Idea That The Present Works Is Structured, With The Proposal Of Making An Analysis And Study Of The Contents Of The Al-F"R"B"'S Political Writings And Investigate The Influence And Assimilation Of The Republic Of Plato In The Work Of This Philosopher. For This Purpose, We Take As Object Of Investigation The Books "On The Views Of The People Of The Ideal City" (Kit"B Ar"" Ahl Al-Madinah Al-F""Ila) And "Guidance On The Path To Happiness" (Kit"B Al-Tanbih `Ala Sab"L Al-Sa`"Da), Seeking To Answer The Following Question: "What, In Effect, Is The Influence Of Plato"S